Anaerobic biodigestion of pigs feces in the initial, growing and finishing stages fed with diets formulated with corn or sorghum - Miranda, Adélia P.; Lucas Junior, Jorge de [UNESP]; Thomaz, Maria Cristina [UNESP]; Pereira, Gener Tadeu [UNESP]; Fukayama, Ellen H. (Associação Brasileira de Engenharia Agrícola (SBEA), 2012)
Objetivou-se avaliar a produção e a qualidade do biogás e do biofertilizante obtidos em biodigestores abastecidos com dejetos de suínos, nas fases inicial, crescimento e terminação, alimentados com dietas formuladas à base de milho ou sorgo. Foram utilizados 20 biodigestores de bancada, com tempo de retenção hidráulica de 30 dias, e cargas diárias que continham 4,0 a 6,0% de sólidos totais (ST) e 3,6 a 5,2% de sólidos voláteis (SV). Nos efluentes dos biodigestores, foram verificados teores médios de ST variando de 1,6 a 2,0% e de SV entre 1,2 e 1,6%. As reduções médias de ST foram de 57,7 a 64,7% e de SV de 61,7 a 69,0%, sendo que houve diferença somente na fase de terminação, na qual as maiores reduções médias foram para biodigestores abastecidos com dejetos de animais alimentados com dietas à base de milho. Nos biodigestores abastecidos com dejetos de animais em fase inicial e de crescimento, alimentados com dietas formuladas à base de milho, foram verificadas maiores produções médias de biogás e os maiores potenciais médios de produção de biogás. Os potenciais médios obtidos foram 0,033; 0,181; 0,685; 0,788 e 1,132 m³ por kg de afluente, estrume, ST adicionados, SV adicionados e SV reduzidos, respectivamente. Não foram verificadas diferenças quanto ao teor médio de metano no biogás entre dietas e fases. As concentrações médias dos nutrientes N, P, K, Ca, Mg, Na, Fe, Mn, Zn e Cu no afluente e efluente dos biodigestores variaram entre as dietas e fases.

The objective of this study was to evaluate the quality and the production of biogas and biofertilizer obtained from biodigester supplied with pig feces in the initial, growing and finishing stages, fed with diets formulated based on corn or sorghum. Twenty bench biodigesters were used with hydraulic retention time of 30 days and daily loads that contained 4 to 6% of total solids (TS) and 3.6 to 5.2% of volatile solids (VS). In the effluent of the biodigesters, mean levels of TS were observed ranging between 1.6 and 2.0% and of VS between 1.2 and 1.6%. The mean reductions of TS were 57.7 to 64.7% and of VS from 61.7 to 69.0%, and there was only difference in the finishing phase, in which the major averages reductions were produced by the biodigesters supplied with feces from animals fed with diets based on corn. In biodigesters supplied with feces from animals in the initial and growing stages fed with diets based on corn, were observed higher average productions of biogas and the greatest average potentials of biogas production. The average potentials obtained were 0.033; 0.181; 0.685; 0.788 and 1.132 m³ per kg of affluent, manure, TS added, VS added and VS reduced, respectively. No differences were found on the average content of methane in the biogas between diets and stages. The average concentrations of nutrients N, P, K, Ca, Mg, Na, Fe, Mn, Zn and Cu in the biodigester affluent and effluent, ranged between diets and stages.
Biodigestão anaeróbia de dejetos de suínos nas diferentes fases alimentados com dietas formuladas com milho ou sorgo
Keywords: biodigesters; Biogas; pig feces; Environmental impact; biodigestores; Biogas; dejetos de suínos; Impacto ambiental